2023
DOI: 10.3390/molecules28062497
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Gas Chromatography-Mass Spectrometry Method for Determining Acaricides in Bee Pollen

Abstract: Pesticides can be found in beehives for several reasons, including contamination from surrounding crops or for their use by beekeepers, which poses a risk to bee ecosystems and consumers. Therefore, efficient and sensitive methods are needed for determining pesticide residues in bee products. In this study, a new analytical method has been developed and validated to determine seven acaricides (atrazine, chlorpyrifos, chlorfenvinphos, α-endosulfan, bromopropylate, coumaphos, and τ-fluvalinate) in bee pollen usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…QuEChERS, a novel technique for determining pesticide residues in food analysis, was developed and validated by Anastassiades et al (2003) [85] and quickly adopted by numerous laboratories to study pesticides in bee products [86,87]. The QuEChERS method uses a combination of liquid-liquid extraction, mainly acidified acetonitrile [9], and solid-phase dispersion sorbents (see Table 4) and salts (e.g., magnesium sulphate or sodium acetate) to extract and then clean the extract.…”
Section: Quechersmentioning
confidence: 99%
See 1 more Smart Citation
“…QuEChERS, a novel technique for determining pesticide residues in food analysis, was developed and validated by Anastassiades et al (2003) [85] and quickly adopted by numerous laboratories to study pesticides in bee products [86,87]. The QuEChERS method uses a combination of liquid-liquid extraction, mainly acidified acetonitrile [9], and solid-phase dispersion sorbents (see Table 4) and salts (e.g., magnesium sulphate or sodium acetate) to extract and then clean the extract.…”
Section: Quechersmentioning
confidence: 99%
“…Over the years, the QuEChERS procedure has been modified and used for the determination of pesticide residues in honey [88], wax [89], pollen [86], bumblebees [90] and royal jelly [9,41,44,91,92]. The insecticide pyriproxyfen and its four metabolites were extracted from royal jelly using the QuEChERS method [70].…”
Section: Quechersmentioning
confidence: 99%
“…However, several studies have shown the presence of contaminants of known toxicity in bee pollen, sometimes reaching potentially dangerous concentrations [ 7 ]. Particularly alarming contaminants found in bee pollen are mycotoxins, toxic metabolites produced by fungi in favorable environmental conditions [ 8 ], and pesticides, commonly employed for pest control, which pose a potential health hazard for consumers [ [9] , [10] , [11] ]. The contamination of bee pollen with such contaminants can have several sources.…”
Section: Introductionmentioning
confidence: 99%